2008
DOI: 10.4161/cc.7.14.6274
|View full text |Cite
|
Sign up to set email alerts
|

Distinct proliferative and transcriptional effects of the D-type cyclins in vivo

Abstract: The D-type cyclins (D1, D2 and D3) are components of the cell cycle machinery and govern progression through G 1 phase in response to extracellular signals. Although these proteins are highly homologous and conserved in evolution, they contain distinct structural motifs and are differentially regulated in various cell types. Cyclin D1 appears to play a role in many different types of cancer, whereas cyclins D2 and D3 are less frequently associated with malignancy. In this study, we transiently expressed cyclin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
68
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 44 publications
3
68
0
2
Order By: Relevance
“…This model is supported by evidence that an siRNA-mediated reduction in cyclin D1 expression during estrogen stimulation leads to a proportional decrease in induction of cyclin E2 and that induction of cyclin D1 is sufficient for increased cyclin E2 expression and E2F1 recruitment to the cyclin E2 gene promoter. Recent evidence that cyclin E2 expression is increased when cyclin D1, D2, or D3 is transiently expressed in hepatocytes provides further support (44).…”
Section: Discussionmentioning
confidence: 81%
“…This model is supported by evidence that an siRNA-mediated reduction in cyclin D1 expression during estrogen stimulation leads to a proportional decrease in induction of cyclin E2 and that induction of cyclin D1 is sufficient for increased cyclin E2 expression and E2F1 recruitment to the cyclin E2 gene promoter. Recent evidence that cyclin E2 expression is increased when cyclin D1, D2, or D3 is transiently expressed in hepatocytes provides further support (44).…”
Section: Discussionmentioning
confidence: 81%
“…Indeed, previous studies have shown that Cyclin D2 can be regulated by multiple mitogenic signals in a number of human cancers, such as leukemia, testicular cancer and ovarian cancer. [20][21][22] Furthermore, whether PITX2 cooperates with other oncogenic signals to upregulate Cyclin D2 in thyroid tumorigenesis remains unclear and warrants further study. Dysregulated (stabilization and translocation of) β-catenin plays a critical role in oncogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Mullany et al reported that cyclin D1 and D2 differentially regulate transcription and proliferaion in hepatocytes. 18 Second may be that target factors of cyclin D1 and D2 is involved for the interaction between cyclin Ds and p21/p27.…”
Section: © 2 0 0 8 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 99%